Arctic archives in old wood: Dendrochronological potential of Svalbard dwarf shrubs from historical polar expeditions - Opała-Owczarek, Magdalena; Greaves, Ciara; Harris, Stephen A.; Owczarek, Piotr; Büntgen, Ulf; Gardiner, Lauren; Zmartzy, Sue; Wawrzyniak, Zuzanna (Polish Polar Research, 2026)
Instrumental climate records from Svalbard are sparse and discontinuous, with most observations beginning in the 20th century, making dendroclimatological reconstructions essential for extending climate information into earlier periods. In the treeless High Arctic, dwarf shrubs constitute the only dendrochronological archive; however, existing shrub-ring chronologies from Svalbard are generally short and largely restricted to the recent past. This study assesses the dendrochronological potential of Arctic dwarf shrubs preserved in historical herbarium collections originating from early polar exploration. We analyzed herbarium specimens of Salix polaris Wahlenb., S. reticulata L., Dryas octopetala L., and Empetrum hermaphroditum Hagerup collected between 1838 and 1898 and stored in major European and North American herbaria. Using modern microanatomical preparation and ring-width measurement techniques, annual growth rings were successfully identified and measured in dried herbarium material. Based on species composition and spatial distribution, three mean ring-width chronologies were developed for southern and central Spitsbergen, extending into periods lacking instrumental climate observations. The time span of the newly developed chronologies is 1803–1928. Although sample replication remains limited and direct calibration with meteorological data is not yet possible, herbarium-based chronologies show coherent growth patterns and reveal intervals of reduced and enhanced growth consistent with independent climate proxies from ice cores, lake sediments, and early meteorological records. These results demonstrate that historical herbarium collections can substantially extend Arctic shrub dendrochronological records and provide climate-sensitive information from ice-free areas of Svalbard.